Improving the Usage Properties of Steel Using Cold Spray Deposition: A Review - Fabian Cezar Lupu; Corneliu Munteanu; Adrian Constantin Sachelarie; Vlad Nicolae Arsenoaia; Bogdan Istrate (Crystals, 2023)
In this paper, the improvement of the characteristics of different steels that are subjected to extreme operating conditions, including the steels used in the manufacture of various military components, the AISI 52100, the manufacture of bearings, and other types of parts that are also subjected to severe operating conditions were analyzed regarding cold spraying, which uses different types of powders to increase the performance of the materials. The cold, thermal spraying technology “Cold Spray” is a method of processing particles in a solid state. Thermal spraying, based on the dynamic increase in gas acceleration up to supersonic speeds, leads to the obtainment of high kinetic energies, and the accelerated particles are deposited at values that are below their melting point. Research conducted through cold spray technology has seen a significant improvement in material properties; when processing the particles in a solid state, they adhere to the surface instead of eroding it. Cold spraying has proven to be an effective technique for improving material properties, as confirmed by its integration into different fields and industries, becoming competitive by being the only method for depositing particles below their melting point.